Parsimonious relations between Guitar Textural Proposals - Pinto, Bernardo Ramos; Gentil-Nunes, Pauxy (Revista Vórtex, 2020)
Guitar Textural Analysis is an analytical proposal devised for the composition for the guitar that exposes the relations between the textural structure and the technical procedures used in the instrumental performance. The Guitar Textural Proposals (GTPs) are the specific configurations extracted in this analytical process. In the present work, the focus remains on recognizing parsimonious movements between GTPs, that is, minimal distinctions between patterns of use of the instrument combined with respective textural configurations. Parsimoniousness is defined in the context of Developing Variation, Neo-Riemannian Theory, and Partitional Analysis. Previous works by Fabio Adour and authors Sérgio Freire and Pedro Cambraia present perspectives on the relation between texture and guitar performance. Leo Brouwer's series of progressive pieces Études Simples is adopted as a reference. The work results in a proposal for a ordered network of technical-textural configurations connected by parsimonious relations.